A Polymerization‐Assisted Grain Growth Strategy for Efficient and Stable Perovskite Solar Cells. Issue 17 (8th March 2020) - Zhao, Yepin; Zhu, Pengchen; Wang, Minhuan; Huang, Shu; Zhao, Zipeng; Tan, Shaun; Han, Tae‐Hee; Lee, Jin‐Wook; Huang, Tianyi; Wang, Rui; Xue, Jingjing; Meng, Dong; et al.
Abstract: Intrinsically, detrimental defects accumulating at the surface and grain boundaries limit both the performance and stability of perovskite solar cells. Small molecules and bulkier polymers with functional groups are utilized to passivate these ionic defects but usually suffer from volatility and precipitation issues, respectively. Here, starting from the addition of small monomers in the PbI2 precursor, a polymerization‐assisted grain growth strategy is introduced in the sequential deposition method. With a polymerization process triggered during the PbI2 film annealing, the bulkier polymers formed will be adhered to the grain boundaries, retaining the previously established interactions with PbI2 . After perovskite formation, the polymers anchored on the boundaries can effectively passivate undercoordinated lead ions and reduce the defect density. As a result, a champion power conversion efficiency (PCE) of 23.0% is obtained, together with a prolonged lifetime where 85.7% and 91.8% of the initial PCE remain after 504 h continuous illumination and 2208 h shelf storage, respectively. Abstract : A polymerization‐assisted grain growth strategy in the sequential deposition method of perovskite thin films is demonstrated by triggering a polymerization process during PbI2 film annealing. This strategy effectively passivates undercoordinated lead ions, reduces defect density, and boosts power conversion efficiency up to 23.0%, together with a prolonged lifetime.